Gut Microbiome as Target for Innovative Strategies Against Food Allergy - Berni Canani, Roberto; Paparo, Lorella; Nocerino, Rita; Di Scala, Carmen; Della Gatta, Giusy; Maddalena, Ylenia; Buono, Aniello; Bruno, Cristina; Voto, Luana; Ercolini, Danilo (Frontiers in Immunology, 2019)
The dramatic increase in food allergy prevalence and severity globally requires effective strategies. Food allergy derives from a defect in immune tolerance mechanisms. Immune tolerance is modulated by gut microbiota structure , and microbiome alterations (dysbiosis) have a pivotal role in the development of food allergy. Environmental factors, including a low-fibre/high-fat diet, caesarean delivery, antiseptic agents, lack of breastfeeding, and drugs can induce the gut microbiome dysbiosis, and have been associated with food allergy. New experimental tools and technologies have provided information regarding the role of metabolites generated from dietary nutrients and selected probiotic strains that could act on immune tolerance mechanisms. The mechanisms are multiple and still not completely defined. Increasing evidence has provided useful information on optimal bacterial species/strains, dosage and timing for intervention. The increased knowledge of the crucial role played by nutrients and gut microbiota-derived metabolites is opening the way to a post-biotic approach in the stimulation of immune tolerance through epigenetic regulation. This review focused on the potential role of the gut microbiome as the target for innovative strategies against food allergy.